Review of Techniques Used For Change Detection in Remotely Sensed Images (International Journal of Engineering and Computer Science, 2017)
he propensity towards up to date information about the earth’s surface is ever increasing. The information generated through the satellites is used in wide range of applications such as land monitoring, whether forecasting, resource monitoring and environment monitoring. Legion of techniques are developed to detect change by utilizing the applications of remote sense data and new techniques through research are still emerging. This paper begins by first of all discussing slandered pixel based techniques and statistics based techniques for change detection. This is preceded by describing object oriented techniques. Data mining approaches for change detection is comprehensively described. The relative merits and demerits of each technique is described to determine optimal methodology to be used in future research.